Digital Marketing Training for MSMEs Sumber Rejeki Bawang in Kediri Regency - Harwida, Gleydis; Tertibi, Yaoma; Novilia, Evita (Jurnal Pengabdian Masyarakat Bestari, 2024)
Digital Marketing Training for Sumber Rejeki Bawang MSMEs in Kediri Regency, aims to increase the understanding and skills of MSME players in utilizing digital technology for product marketing. This activity involved the owner and employees of Sumber Rejeki Bawang MSME. The training included an introduction to social media and marketplaces, content marketing techniques, and search engine optimization (SEO). Through a workshop and hands-on approach, participants were trained to utilize digital platforms such as Instagram, Facebook, Shoppe, and Tokopedia to expand their market and improve the competitiveness of their products. The training results showed that participants experienced a significant increase in their understanding of the use of digital marketing, with most starting to utilize social media and marketplaces as marketing channels. Overall, this training can improve the marketing capacity of Sumber Rejeki Bawang MSMEs and open up opportunities to expand the market, both locally and nationally.